Navigating the shift in Bangladeshi host community’s perceptions towards the Rohingya refugees: a declining sympathy - Kamruzzaman, Palash; Siddiqi, Bulbul; Ahmed, Kajal (Frontiers in Sociology, 2024)
Generosity and selflessness from the host community in Cox’s Bazar were deemed to be instrumental in supporting Rohingyas who sought refuge in Bangladesh in 2017. Thousands of Rohingyas had to flee from their own country to save lives due to state-supported military violence. Initially, Bangladeshi media and civil society were largely supportive of the Rohingyas. However, the initial sympathy later withered away and may have turned into frustration and hostility. Based on 39 in-depth interviews with hot community members and humanitarian professionals, this paper argues that protraction of the crisis, inability to access natural resources due to the refugee camps, some Rohingyas’ involvement in various unlawful activities, a perceived sense of neglect from the international community, and disruption in local labour market/trade affecting cost of living conditions for low-income people seem to have played important roles in creating widespread tensions between the host community and Rohingya refugees. We contend that findings of this study will add to the critical scholarship of humanitarian development in deepening the understanding of host and refugee communities’ relationships. This paper will also have a positive impact on future policies toward harmonious coexistence between host communities and displaced refugees and potential sustainable solutions to the crisis.